2023
DOI: 10.1371/journal.pone.0284762
|View full text |Cite
|
Sign up to set email alerts
|

Are we seeing the unseen of human trafficking? A retrospective analysis of the CTDC k-anonymized global victim of trafficking data pool in the period 2010–2020

Abstract: Background Human trafficking is considered a hidden global crime with unsubstantiated numbers. Despite the challenges in counting or measuring this crime, reports revealed the presence of around 40.3 million victims worldwide. Human trafficking results in severe detrimental impacts on both mental and physical health. Given the sensitivity and negative consequences of human trafficking on the global system and victims, and considering the scarce research in this area, our current study aimed at describing the (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Human trafficking is widely considered a hidden global crime, and the number of cases varies drastically among surveys (McDonald, 2014). Nevertheless, research has indicated that labor trafficking is at least as serious a crime as sex trafficking, occurring behind the closed doors of industries and workplaces worldwide (Al-Tammemi et al, 2023). A report by International Labour Organization (ILO), Walk Free, and International Organization for Migration (IOM) states that there are 17.3 million privately imposed forced labors worldwide and 6.3 million forced commercial sexual exploitations (ILO et al, 2022).…”
Section: Misconceptions About Human Traffickingmentioning
confidence: 99%
“…Human trafficking is widely considered a hidden global crime, and the number of cases varies drastically among surveys (McDonald, 2014). Nevertheless, research has indicated that labor trafficking is at least as serious a crime as sex trafficking, occurring behind the closed doors of industries and workplaces worldwide (Al-Tammemi et al, 2023). A report by International Labour Organization (ILO), Walk Free, and International Organization for Migration (IOM) states that there are 17.3 million privately imposed forced labors worldwide and 6.3 million forced commercial sexual exploitations (ILO et al, 2022).…”
Section: Misconceptions About Human Traffickingmentioning
confidence: 99%
“…Most victims of human trafficking are not reported; this results from language barriers experienced by the victim and from the victim's fear of both law enforcement and the trafficker. Importantly, individuals who participate in providing medical care can potentially identify and provide resources for human trafficking victims [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Trafficking in human beings predominantly occurred in women (70%) and children. The most frequent age groups included children ranging from nine to 17 years (11.9%), followed by victims between the ages of 30 to 38 years (9.8%); however, for more than half of the victims (53%), the age was unknown [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation